Food : in context - Lerner, Brenda Wilmoth; Lerner, K. Lee (In context (Gale (Firm)), 2011)
Food: In Context examines food in relationship to nutrition, world health issues, agriculture, environmental concerns, current events and political decision-making. Written by experts in nutrition, medicine, culinary arts, agriculture/aquaculture, environmental science and history, this full-color set covers the historical, political and ethical debates related to food. It also explores how food impacts daily life, trade and commerce, the environment, and health and nutrition. --from publisher description